Descriptions of the final stadium larva and female adult of Coeliccia mingxiensis Xu (Odonata: Zygoptera: Platycnemididae) - Xu, Qi-Han (Zootaxa, 2013)
The final stadium larva of Coeliccia mingxiensis Xu is described and illustrated. The female adult is also described for the first time. The larva can be easily separated from all known Coeliccia larvae by the following distinct morphological characters : (1) prementum longest in all known Coeliccia larvae; median lobe with 4 pairs of premental setae and palpal lobe with 6 palpal setae; (2) caudal gills shortest of all known Coeliccia larvae when compared with body length; median gill rounded at apex and lateral gill with a small median projection at apex. The female is similar to the male in many respects, differing chiefly in several respects as follows: the transverse yellow band on vertex of head broader and straighter than in male; antehumeral stripe on mesepisternum somewhat incurved basally, not forming a strong hook, which is present in male; distal abdomen with obviously different colour pattern; anal appendages brownish-black, shorter than S10; vulvar scales robust, brownish-yellow, projecting well beyond end of abdomen.